Harnessing the power of botanical gardens: Evaluating the costs and resources needed for exceptional plant conservation - Megan Philpott; Valerie C. Pence; Burgund Bassüner; Ashley S. Clayton; Emily E. D. Coffey; Jason L. Downing; Christine E. Edwards; Raquel Folgado; Jason J. Ligon; Christy Powell; Joseph Francis Ree; Alexandra E. Seglias; et al. (Applications in Plant Sciences, 2022)
Abstract Premise The effective ex situ conservation of exceptional plants, whether in living collections or cryo‐collections, requires more resources than the conservation of other species. Because of their expertise with rare plants, botanical gardens are well positioned to lead this effort, but a well‐developed strategy requires a clear understanding of the resources needed. Methods Grant funding was obtained from the Institute of Museum and Library Services to support a three‐year project on cryobanking, and to provide smaller grants to 10 other botanical gardens for one‐year projects on either (1) seed behavior studies or (2) the development of protocols for in vitro propagation or cryopreservation. Results Nine of the partner gardens worked on 19 species (one was unable to continue due to the COVID‐19 pandemic), while the larger project focused on 14 species. A point system was developed for tasks accomplished, and the average costs per point of the larger and smaller projects were similar. Labor accounted for half the costs. Projects focused on species in the Asteraceae and Orchidaceae had lower costs per point than other species. Discussion Both large and small projects can contribute to a strategy for exceptional plant conservation for similar costs. Prioritizing species with lower costs could help advance the field while allowing time for work on more difficult species to develop.